2021
DOI: 10.1002/joc.7125
|View full text |Cite
|
Sign up to set email alerts
|

Declining North American snow cover ablation frequency

Abstract: At a continental scale, trends in aggregate ablation frequency inform changes in snow cover extent, however the variability and trends in the frequency and magnitude of snow ablation events at regional scales are less well understood. Determining such variability is critical in describing regional hydroclimate, where snow ablation can influence streamflow, soil moisture and groundwater supplies. This study uses a gridded dataset of United States and Canadian snow ablation events derived from 1960 to 2009 surfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 44 publications
1
1
0
Order By: Relevance
“…The southwest‐to‐northeast increasing gradient of both snow ablation and rain‐on‐snow ablation event frequency observed here is similar to that observed by other studies in the literature that used different approaches (Jeong & Sushama, 2018; Li et al, 2019; Suriano, 2022; Suriano et al, 2021; Wachowicz et al, 2020; among others). For instance, Wachowicz et al (2020) evaluated rain‐on‐snow event frequency seasonally for the eastern United States, inclusive of the ORB, using a 1° gridded snow depth product.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The southwest‐to‐northeast increasing gradient of both snow ablation and rain‐on‐snow ablation event frequency observed here is similar to that observed by other studies in the literature that used different approaches (Jeong & Sushama, 2018; Li et al, 2019; Suriano, 2022; Suriano et al, 2021; Wachowicz et al, 2020; among others). For instance, Wachowicz et al (2020) evaluated rain‐on‐snow event frequency seasonally for the eastern United States, inclusive of the ORB, using a 1° gridded snow depth product.…”
Section: Discussionsupporting
confidence: 90%
“…Prior research has suggested there is evidence U.S. snowfall totals have decreased, and will continue to decrease, with time despite stationary or increasing trends in total precipitation, as less precipitation occurs as snowfall (Notaro et al, 2014; among others). This may yield mixed rain‐on‐snow frequency signals, as less snowfall would result in a thinner snowpack that could be completed ablated more quickly, thus the potential for fewer rain‐on‐snow events once the snowpack is exhausted (Suriano et al, 2021). This aligns with research that suggests snow cover and snow mass has decreased across North America over time (Mudryk et al, 2020).…”
Section: Discussionmentioning
confidence: 99%